The Effect of Enhancement on Trained Panel Beef Palatability Scores Is Dependent Upon USDA Quality Grade - K. V. McKillip; A. K. Wilfong; J. M. Gonzalez; T. A. Houser; E. A. Boyle; J. A. Unruh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2016)
Quality grades are used to determine beef value. The U.S. Department of Agriculture grading system categorizes beef into levels of eating satisfaction with the highest being Prime and decreases until reaching the Canner quality grade. Currently the premium of Prime graded carcasses over Select is 16.73 (USDA, 2015). Traditionally, USDA Select cuts are known to have lower palatability ratings for juiciness, tenderness, and overall liking. Select steaks also fail to meet consumer eating expectations more than 33% of the time (Corbin, 2015). This failure rate represents a large cost for the industry. Product enhancement utilizing a water, salt, and phosphate solution is commonly used in the pork and poultry industries to increase product eating satisfaction. This technology offers an opportunity for the beef industry to improve palatability as well. Previous research has shown enhancing beef results in a higher juiciness, tenderness, and overall liking ratings by consumers and trained panelists (Pietrasik and Janz, 2009). Previous research has shown enhancing Select cuts results in products that rate similar to Prime (Woolley, 2015). To date, it is unknown if enhancement of higher quality beef (Choice and Prime) results in the same increase in palatability observed in lower quality cuts. Therefore, the objective of this study was to determine the effect of enhancement on trained panel beef palatability scores of strip loins of three quality grades when cooked to three degrees of doneness.
Keywords: enhancement; palatability; grade